2012
DOI: 10.21273/hortsci.47.5.603
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Inoculant Increases Yield of Spice Pepper and Affects the Indigenous Fungal Community in the Field

Abstract: Although the majority of horticultural crops are mycorrhiza-dependent, the role of arbuscular mycorrhizal (AM) inoculation in plant production has been neglected in high-input agriculture. Field application of a commercial inoculum mix of Glomus spp. was tested in spice pepper (Capsicum annuum L. var. longum), cv. Szegedi, cultivation. With polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP), diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…During the last decades, several molecular techniques have been used to characterize entire communities of mycorrhiza in soil [144,145] and AMF inocula [146][147][148]. These techniques enable to monitor the introduced fungal symbiont both inside and outside the host during plant growth [149,150].…”
Section: Challenges Of Amf Applicationmentioning
confidence: 99%
“…During the last decades, several molecular techniques have been used to characterize entire communities of mycorrhiza in soil [144,145] and AMF inocula [146][147][148]. These techniques enable to monitor the introduced fungal symbiont both inside and outside the host during plant growth [149,150].…”
Section: Challenges Of Amf Applicationmentioning
confidence: 99%
“…For example, where plants must first be propagated in nurseries prior field transplantation, uninoculated "controls" typically perform more poorly than inoculated plants (e.g. Camprubi et al, 2015;Hernádi, Sasvári, Albrechtová, Vosátka, & Posta, 2012;Tawaraya et al, 2012). In this situation, control plants are deprived of the AM symbiosis during critical developmental stages, and do not provide a valid control.…”
Section: Inappropriate Controlsmentioning
confidence: 99%
“…It colonizes the host's roots to create a mutually beneficial relationship without causing any harm. According to Menge (1985), Finlay (2008), Hernadi et al (2012), and Zasvari et al 2012, the hosts obtain nutrients and water from mycorrhiza, while the fungi, in turn, obtain carbohydrates or nutrition from the hosts. Smith and Read (2008), Lee et al (2012), and Yinan et al (2017) reported that mycorrhizae enhance plant growth because it increases its ability to obtain water and nutrients such as phosphorus, nitrogen, and potassium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mycorrhiza is capable of increasing host resistance to root pathogens (Pozo et al 2010), increasing host tolerance to environmental stress due to salinity and drought (Latef et al 2016;Quiroga et al 2017), and heavy metal contamination (Upadhyaya et al 2010). Moreover, mycorrhizal abundance and activities in the soil rhizosphere are largely determined by climate, host type, and soil water content or drought level (Schubler et al 2001;Moreira et al 2007;Hernadi 2012;Sadhana 2014;Quiroga et al 2017;Mathimaran et al 2017;Choosa-nga et al 2019), type and level of soil fertility, as well as altitude (Allen and Boosalis, 1983;Tahat and Sijam 2012;Kavitha and Nelson 2013;Mo et al . 2016).…”
Section: Introductionmentioning
confidence: 99%